Integration Model of ISO 14001 with Lean Principles - A. P., Puvanasvaran; M. R. , Muhamad (©2012 Science Publication, 2012)
Lean principles and ISO 14001 are key business process strategies which are employed by companies to enchance their manufacturing performance and business efficiencies. The primary objective of the paper is to provide a conceptual framework through an effective integration of these two systems for enhanced business efficiency and productivity. The research methodology applied in the context of this study is based on preliminary literature review of ISO 14001 standards and Lean Principles. The findings contributed to the framing of new conceptual framework that combines the benefits of both Lean Principles and ISO 14001 principles for enhanced business efficiencies and continual improvement. This study concluded that the intergration of lean principles into ISO 14001 will serve pratical methods for ISO 14001 to achieve the continual improvement.